Democratizing higher education: Navigating public accountability for equity, inclusivity, and social Justice - Hart, C.; Daniels, P.; September-Brown, P. (South African Journal of Higher Education, 2025)
South Africa’s transformation agenda places increasing emphasis on the democratization of higher education, particularly with regard to institutional accountability and the advancement of equity, inclusivity, and social justice. This article examines how public accountability intersects with the broader goals of democratic reform within Higher Education Institutions (HEIs), presenting the University of the Western Cape (UWC) as a case study. Through an analysis of UWC’s Community Engagement Strategy, most notably its Scholarship of Engagement Model and the Scholarship of Engagement for Societal Impact (SoE-SI) framework, the article explores how principles of social justice, inclusion and equity are operationalized in both academic and societal contexts. It further interrogates the layered dynamics of accountability in a transforming HE landscape, where transparent responsiveness to diverse stakeholders must be weighed against institutional autonomy. The article also considers the role of UWC’s SoE-SI Knowledge Management System (KMS) Web Portal in measuring and evaluating the institution’s contribution to societal transformation. Recommendations highlight the importance of sustained transparency, responsiveness, and co-constructed dialogue to strengthen public accountability and embed social justice within institutional practices.